2020
DOI: 10.1177/1054773820928197
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Quality of Life in Young Adults Diagnosed With Cancer

Abstract: A cross-section correlational study was conducted to evaluate the overall quality of life in young adults (AYAs) diagnosed with cancer, and the impact of health-related and non-health-related factors on their quality of life. Fifty-six AYA cancer survivors were recruited to elicit the impact of biological function (cancer type and comorbidity), symptoms, functional status, general perception of health status, gender, and characteristics of the environment on quality of life. Participants experienced higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This supports the qualitative findings. However, the majority of current articles that address factors that impact occupational engagement emphasize the physical aspects such as symptom management (Kaal et al, 2021; McKie & Laiyemo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This supports the qualitative findings. However, the majority of current articles that address factors that impact occupational engagement emphasize the physical aspects such as symptom management (Kaal et al, 2021; McKie & Laiyemo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…38 Likewise, another study from the United States proved this correlation. 39 After controlling for health perception and selected demographic characteristics, adherence to physical activity was a positive significant predictor of quality of life, and this indicates that the higher the commitment to physical activity, the better the quality of life for mothers. Consistent with these results, it was found that working moms in Tunisia could considerably increase their health-related quality of life by participating in physical activity, which could help to mitigate adverse health-related outcomes.…”
Section: Dovepressmentioning
confidence: 95%
“…Given that studies in the general cancer population support a strong correlation between supportive care service receipt and cancer outcomes, 6,7 we conducted our study with the hypothesis that residential location may affect receipt of supportive care services and thus contribute to the poorer survival seen in rural YAs. We also sought to study the impact of residential location on treatment satisfaction as both supportive care service receipt and treatment satisfaction have been linked to quality of life, [31][32][33][34] and there is limited work comparing these metrics or their impact by residential location.…”
Section: Introductionmentioning
confidence: 99%